Three Layers of Meaning in Tolerance Verses in Mori Sama - Khairiyah, Misbahul; Qudsy, Saifuddin Zuhri (QOF, 2022)
Tolerance is a prominent issue amid Indonesia's efforts to moderate everyday attitudes towards religion and statehood. Understanding it is continuously explored through the values of the Qur'an, Hadith, and local traditions existing in society. Mori Sama in Donggo, Mbawa, is a tradition with values of tolerance legitimized by the Qur'anic texts according to its indigenous leaders. This paper explores the Donggo Mbawa community's understanding of tolerance, examining how they interpret tolerance verses and their practical implementation. As a form of field research, this paper relies on observation and interviews as primary data sources. Applying Karl Manheim's analysis through the theory of meaning, the study concludes that the Mbawa community upholds the principle of mori sama, stemming from a common ancestry. With the introduction of Islam and other religions to Donggo, the Mbawa community began to separate based on their respective beliefs. Secondly, the understanding of Islamic religious figures in Donggo Mbawa and the community towards tolerance verses is manifested in mutual respect, appreciation, and acceptance of differences. For example, village events such as weddings, circumcisions, communal prayers, Hajj prayers, Kasaro ceremonies, and religious holidays. Thirdly, the meaning of tolerance verses in the understanding of Islamic religious figures and the Mbawa community is generally grounded in the ancestral principle of Mori Sama.